Optoacoustic sensing of hematocrit to improve the accuracy of hybrid fluorescence-ultrasound intravascular imaging - Bozhko, Dmitry; Karlas, Angelos; Gorpas, Dimitris; Ntziachristos, Vasilis (Journal of Biophotonics, 2018)
Hybrid intravascular fluorescence-ultrasound imaging is emerging for reading anatomical and biological information in vivo. By operating through blood, intravascular near-infrared fluorescence (NIRF) detection is affected by hemoglobin attenuation. Improved quantification has been demonstrated with methods that correct for the attenuation of the optical signal as it propagates through blood. These methods assume an attenuation coefficient for blood and measure the distance between detector and the vessel wall by observing the intravascular ultrasound images. Assumptions behind the attenuation employed in correction models may reduce the accuracy of these methods. Herein, we explore a novel approach to dynamically estimate optical absorption by using optoacoustic (photoacoustic) measurements. Adaptive correction is based on a trimodal intravascular catheter that integrates fluorescence, ultrasound and optoacoustic measurements. Using the novel catheter, we show how optoacoustic measurements can determine variations of blood absorption, leading to accurate quantification of the detected NIRF signals at different hematocrit values.
CRIS-Team Scopus Importer:2023-03-08
Keywords: intravascular ultrasound; multimodal imaging; near-infrared fluorescence; photoacoustic; quantitative imaging